Effect of Papaya Seed Extract (Carica papaya Linn.) on Glucose Transporter 4 (GLUT 4) Expression of Skeletal Muscle Tissue in Diabetic Mice Induced by High Fructose Diet - Devyani Diah Wulansari; Achmad Basori; Suhartati Suhartati (Faculty of Pharmacy, Universitas Gadjah Mada, 2017)
Ethnobotany surveys show that papaya seeds are widely used as herbs for the management of some diseases such as abdominal discomfort, pain, malaria, diabetes, obesity, and infection. This research was conducted to analyze the effect of papaya seed extract on GLUT4 expression on skeletal muscle tissue of DM type II model induced by high fructose diet. This study used 24 animals, divided into 4 groups of negative control group, treated with papaya seed extract 100 mg / kgBB, 200 mg / kgBW and 300 mg / kgBW, was adapted for 14 days then induced by fructose solution 20% Orally with a dose of 1.86 grams / kgBB for 56 days. The treatment group was given papaya seed extract in accordance with the dose of each group for 14 days. GDP levels was measured using a spectrophotometer. Skeletal muscle tissue is used on the gastrocnemius part. GLUT4 expression was measured through a Immunoreactive Score (IRS) method with immunohistochemical staining using GLUT4 polyclonal antibodies. Comparative test results showed that there were significant differences between groups (p <0.05) in final GDP variables and GLUT4 expression. Pearson correlation test results show that the value p = 0.001, meaning there is a significant relationship between GLUT4 expression with final GDP levels. The result of simple linear regression analysis showed that p = 0,000 (<0,05), meaning that dose of papaya seed extract had a significant influence on GLUT4 expression.